Increasing International capacity for cscl: coreflect, an example of sharing and adapting cscl environments across europe - Iolie Nicolaidou; Herodotou, Christothea; Kyza, Eleni A. (My University, 2011)
We report on differences in collaborative processes that took place when CSCL environments originally developed in one European country were adapted and enacted in another European country as part of the Digital Support for Inquiry, Collaboration, and Reflection on Socio-Scientific Debates (CoReflect) project. We describe what differences were designed and emerged as part of the adaptation process, and discuss implications for principles for cross-national adaptation of CSCL environments.
Keywords: Europe; Electronics